2011
DOI: 10.1038/ijir.2011.35
|View full text |Cite
|
Sign up to set email alerts
|

Escitalopram treatment for premature ejaculation has a negative effect on semen parameters

Abstract: The aim of this study was to determine the impact of long-term escitalopram treatment on semen parameters of patients with lifelong premature ejaculation (PE). Between November 2008 and January 2010, patients admitted to urology outpatient clinic with a self-reported complaint of PE were evaluated. Medical and sexual history of patients were recorded and patients with lifelong PE (a total of 25 patients) who met the International Society of Sexual Medicine definition were asked to record their intravaginal eja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 36 publications
(36 reference statements)
0
34
0
2
Order By: Relevance
“…35 The single study, which demonstrates the impact of chronic SSRI treatment on semen parameters of lifelong PE patients, revealed semen parameters, which were initially normal. 13 At the end of the 12-week escitalopram treatment, a significant decrease in sperm concentration, motility and normal sperm morphology was demonstrated. This prospective study revealed that prolonged SSRI treatment induced further deterioration in all the major semen parameters (concentration, motility, morphology).…”
Section: Adverse Effects Of Ssri On Semen Parametersmentioning
confidence: 93%
“…35 The single study, which demonstrates the impact of chronic SSRI treatment on semen parameters of lifelong PE patients, revealed semen parameters, which were initially normal. 13 At the end of the 12-week escitalopram treatment, a significant decrease in sperm concentration, motility and normal sperm morphology was demonstrated. This prospective study revealed that prolonged SSRI treatment induced further deterioration in all the major semen parameters (concentration, motility, morphology).…”
Section: Adverse Effects Of Ssri On Semen Parametersmentioning
confidence: 93%
“…Administration of escitalopram (daily dosage 10 mg) to patients with lifelong premature ejaculation for 12 weeks has been associated with a significant decrease in sperm concentration, motility and morphology, when compared with baseline semen measures (10). Further investigations suggest that SSRIs can impair semen quality and damage sperm DNA integrity in depressed fertile men (11).…”
Section: Previous Clinical Observationsmentioning
confidence: 97%
“…Preclinical investigations in experimental animals indicate that a range of antidepressants can have untoward effects on spermatogenesis and sperm viability (2-7). Observations from a limited number of case series and case reports together suggest that antidepressant drug treatment can be associated with abnormal spermatogenesis and male infertility (8)(9)(10)(11)(12)(13). We report the case of a 30-year-old man who was found to have abnormal sperm parameters during treatment with the selective serotonin reuptake inhibitor (SSRI) citalopram, which resolved once citalopram was withdrawn: subsequent treatment with the novel antidepressant agomelatine (a melatonin agonist and 5-HT2C receptor antagonist) was not found to be associated with abnormal sperm parameters.…”
Section: Introductionmentioning
confidence: 97%
“…Akılda tutulması gereken bir konu olarak çocuk isteyen çiftler için SSRI'ların uzun süreli kullanımlarında sperm motilitesine, sperm DNA sına zarar verebileceğidir. Bu duruma sebep olan mekanizmalar tam olarak aydın-latılamamış olmasına rağmen fertilite üzerine negatif etkisi çalışmalarla ortaya konulmuştur [15][16][17].…”
Section: Si̇stemi̇k İlaçlar Seratonin Geri Alım Inhibitörleriunclassified